Diversity and Evenness of Medicinal Plants in Bantarbolang Nature Reserve Block 19-21, Pemalang, Central Java - Mufadila Day Muhyi; Edy Yani; Pudji Widodo (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
This study was conducted in Bantarbolang Nature Reserve located in Kebon Gede village, Bantarbolang sub-district, Pemalang Regency. Bantarbolang is one of the nature reserves that have the structure and composition of complex vegetation so that there is a diversity of plants which can grow in a conservation area, such as medicinal plants diversity. The objectives of this study were to know the various species of medicinal plants in the Bantarbolang nature reserve block 19-21 and to know the evenness of medicinal plants in the Bantarbolang nature reserve block 19-21. This study was conducted with survey methods and sampling using a systematic square plot. The variables observed consists of dependent variables i.e. the species of medicinal plant and independent variables include environmental factors i.e. temperature, light intensity, humidity, canopy cover, and soil pH. The parameters observed are the number of species and individual number of medicinal plants. The data were analyzed using the Important Value Index (IVI), Diversity Index (H'), Evenness Index (e) and Similarity Index (IS). The plant samples were made into voucher herbarium and stored in PUNS for future references. The results of the study showed that the diversity of medicinal plants in the Bantarbolang Nature Reserve Block 19-21 was high (H’≥0) with 48 species from the 33 families of medicinal plants. Evenness of medicinal plants in Bantarbolang nature reserve block 19-21 is low (e closer to 0). Alocasia cucullata is a dominant species of medicinal plant of a distance of 0-200 meters from the forest edge. Keywords: Bantarbolang nature reserve, diversity, medicinal plant